2017
DOI: 10.1371/journal.pone.0168258
|View full text |Cite
|
Sign up to set email alerts
|

Conflict of Interest Policies at French Medical Schools: Starting from the Bottom

Abstract: BackgroundMedical faculties have a role in ensuring that their students are protected from undue commercial influence during their training, and are educated about professional-industry interactions. In North America, many medical faculties have introduced more stringent conflict of interest (COI) policies during the last decade. We asked whether similar steps had been taken in France. We hypothesized that such policies may have been introduced following a 2009–2010 drug safety scandal (benfluorex, Mediator) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(51 citation statements)
references
References 20 publications
0
47
0
3
Order By: Relevance
“…Our methodology built upon criteria used in earlier studies on COI policies such as the American Medical Students Association (AMSA) scorecard (29), the Canadian scorecard by Shnier et al (27), and the French conflict of interest ranking by Scheffer et al (28) A list of the 38 German medical schools was obtained from the website of the German Medical Faculty Association (Medizinischer Fakultätentag) (31). After formal exchange with a member of the German Ethics Council about the nature of this study, which only involves policies at an institutional level rather than patient data or other personal information, it was deemed unnecessary to ask for formal approval from an ethics committee.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Our methodology built upon criteria used in earlier studies on COI policies such as the American Medical Students Association (AMSA) scorecard (29), the Canadian scorecard by Shnier et al (27), and the French conflict of interest ranking by Scheffer et al (28) A list of the 38 German medical schools was obtained from the website of the German Medical Faculty Association (Medizinischer Fakultätentag) (31). After formal exchange with a member of the German Ethics Council about the nature of this study, which only involves policies at an institutional level rather than patient data or other personal information, it was deemed unnecessary to ask for formal approval from an ethics committee.…”
Section: Methodsmentioning
confidence: 99%
“…Some of this research encouraged change among medical schools so that in 2014, 136 of 160 US medical schools had an existing policy on COI (29). In November of 2017, after a study was published which found no existing policies at any of the French medical schools (28), the French Deans' Conference of Medicine and Odontology Schools published an "Ethical and deontological Charter" (30) -effectively a COI policy for all French medical schools on a national level. In Germany, Lieb et al found that in 2013 only two medical schools reported having a COI policy (21).…”
Section: The Role Of Conflict Of Interest Policies At Medical Schoolsmentioning
confidence: 99%
See 2 more Smart Citations
“…Elles ont été reprises par l'Association nationale des étudiants en médecine de France, en partenariat avec le collectif Formindep, qui prône « une formation médicale indé-pendante au service des seuls professionnels de santé et des patients » [18] . Réagissant à la publication d'une étude issue de cette initiative, qui montrait que les facultés de médecine françaises s'étaient jusqu'à pré-sent peu préoccupées de vérifier la transparence des relations entre les universités et l'industrie pharmaceutique [19] , la Conférence des doyens des facultés de médecine, par la voix de son président, a promis d'engager des actions afin de « garantir l'indépen-dance des formations de toute interférence commerciale » [20] . En contexte nord-américain, de telles politiques sont édictées publiquement depuis plusieurs années, comme c'est le cas par exemple à l'Université Laval à Québec, qui met aussi l'accent sur la notion d'indépendance, en l'élargissant en l'occurrence à la notion « d'indépendance intellectuelle » [21] .…”
Section: Une Problématique éDucationnelle Complexe Et Des Solutions Nunclassified